Cloud IoT systems for smart agricultural engineering - Krishnan, Saravanan, 1982-; Rose, J. Bruce Ralphin; Rajalakshmi, N. R.; Prasanth, N. Narayanan (Boca Raton, FL : Chapman & Hall/CRC Press, 2022)
"This book presents a detailed exploration of adaption and implementation of cloud IoT systems in the field of agriculture. Agro IoT bridges the gap between the conventional agricultural methods and modern technologies. Recently, cloud computing, IoT, big data, machine learning & deep learning technologies are initiated to adopt in the smart agricultural engineering. This edited book covers all the aspects of the smart agriculture with state-of-the-art Cloud IoT systems in the complete 360 degree view spectrum. This book is aimed primarily at graduates, researchers and practitioners who are engaged in agriculture engineering"--
Cloud IoT Applications in Agricultural EngineeringRaj Kumar M, Ahir P.B, Mrinmoy D, Utkarsh KUrban and Vertical farming using Agro Iot system. The Ingredient revolution - A Sustainable Production System for Urban PopulationGokul Anand K.R, Boopathy S, Poornima T, Sharmila A, Dhivya Priya E LSustainable Smart Crop Management for Indian Farms using Artificial IntelligenceSuriya Murugan, Dr.M.G.Sumithra, V.Chandran Smart Livestock Management using Cloud IoTDr. T. Vigneswari, Dr. N. Vijaya GIS Systems for Precision Agriculture and Site-Specific FarmingM. Kavitha, R. Srinivasan, R. KavithaMachine Learning approaches for Agro IoT systemsShriya A. Jadhav, Anisha M. LalA Survey on Internet-of-Things (IoT) based Precision agriculture - Aspects and TechnologiesR. Srinivasan, M.Kavitha, R. Kavitha, K.SaravananNovel Semantic Agro Intelligent IoT System using Machine LearningDr. C.S.Saravana Kumar, Dr. S.Vinoth KumarYield Prediction based on Soil Content Analysis through Intelligent IoT system for Precision AgricultureK. Selvakumar, P. J. A. Alphonse, L. SaiRameshFuzzy Based Intelligent Crop Prediction Over Climate Fluctuation Using IoTSangeetha Subramani, Chandru Vignesh C, Alfred Daniel J, Sivaparthipan C.B, Balaanand Muthu, Suganthi NApplication of Drones with variable area nozzle for Effective Smart Farming activitiesJ. Bruce Ralphin Rose, Saravana Kumar. V, Gopinathan. V TStandards and Protocols for Agro IoTMythili S, Nithya K, Krishnamoorthi M and Kalamani MResearch Issues and Solutions in Agro IoTN Vijaya, T. VigneswariRenewable energy sources for modern agricultural trendsS. Arulvel, T. Joshva Devadas, D. Dsilva Winfred Rufuss, M. Amutha PrabakarSPLARE: A Smart Plant Healthcare SystemSrishti Lodha, Harsh Malani, Narayanan Prasanth, Saravanan K
OCLC-licensed vendor bibliographic record.
Keywords: Agricultural engineering; Internet of things -- Agricultural applications; Agricultural innovations; COMPUTERS / Computer Engineering